IL-4 enhances IL-10 production in Th1 cells: implications for Th1 and Th2 regulation - Mitchell, Ruth E.; Hassan, Masriana; Burton, Bronwen R.; Britton, Graham; Hill, Elaine V.; Verhagen, Johan; Wraith, David C. (Nature Publishing Group, 2017)
IL-10 is an immunomodulatory cytokine with a critical role in limiting inflammation in immune-mediated pathologies. The mechanisms leading to IL-10 expression by CD4+ T cells are being elucidated, with several cytokines implicated. We explored the effect of IL-4 on the natural phenomenon of IL-10 production by a chronically stimulated antigen-specific population of differentiated Th1 cells. In vitro, IL-4 blockade inhibited while addition of exogenous IL-4 to Th1 cultures enhanced IL-10 production. In the in vivo setting of peptide immunotherapy leading to a chronically stimulated Th1 phenotype, lack of IL-4Rα inhibited the induction of IL-10. Exploring the interplay of Th1 and Th2 cells through co-culture, Th2-derived IL-4 promoted IL-10 expression by Th1 cultures, reducing their pathogenicity in vivo. Co-culture led to upregulated c-Maf expression with no decrease in the proportion of T-bet+ cells in these cultures. Addition of IL-4 also reduced the encephalitogenic capacity of Th1 cultures. These data demonstrate that IL-4 contributes to IL-10 production and that Th2 cells modulate Th1 cultures towards a self-regulatory phenotype, contributing to the cross-regulation of Th1 and Th2 cells. These findings are important in the context of Th1 driven diseases since they reveal how the Th1 phenotype and function can be modulated by IL-4.